Psychological characteristics in patients with non-cardiac chest pain - Nikolic, Gordana Miodrag; Mandic Gajic, Gordana; Tasic, Ivan; Zikic, Olivera; Tosic Golubovic, Suzana (Vojnosanitetski pregled, 2021)
Background/Aim. Chest pain of no heart origin resembles angina and when none medical reason is found, the patients are referred to psychiatrist for further assessment. The aim of this reserch was to determine psychological characteristics of the patients with non-coronary chest pain (NCCP), difference compared to the coronary patients and the predictive value of those parameters for NCCP. Methods. Fourty consecutively recruited patients without a diagnose of heart disease (NCCP group) were examined and compared to 45 coronary patients (C group). For psychiatric diagnose, the Mini-International Neuropsychiatric Interview (MINI) was used. Psychological symptoms were assessed by the Symptom Checklist-90-Revised (SCL-90R), exposure to life events was scored by the Holms &Rahe Scale and levels of anxiety and depressiveness by the Back Anxiety Inventory and Back Depression Inventory. The statistical analysis was done by using the software package SPPS17. The Student’s-t test and χ2-test were used for estimating more difference between groups while ANOVA determined parameters associated with NCCP. Results. The NCCP patients were younger (33.40 ± 5.43 vs. 48.37 ± 6.43, p < 0.001), more anxious (20.47 ± 11.93 vs. 9.63 ± 3.86, p < 0.001), had more exposure to life events (102.03 ± 52.22 vs. 46.5 ± 55.08, p < 0.001) and were more distressed (41.37 ± 7.70 vs. 29.37 ± 5.67, p < 0.001), while coronary patients were more depressed and hostile. The regression analysis indicated that elevation in anxiety score for 1 point, means 25% of a higher chance [odds ratio (OR) = 1.25; 95% confidence interval (CI): 1.10–1.41] and elevation in the Life events score, means 2% of a higher chance that subject belonged to the NCCP group (OR = 1.02; 95% CI: 1.01–1.03). The younger subjects were more likely to have non-cardiac chest pain (OR = 0.58, 95% CI: 0.42–0.80). Conclusion. The results suggested that the patients with NCCP had none associated psychiatric disorder, but showed higher distress level, more exposure to negative life events and moderate anxiety level. Psychological help could be of a benefit to prevent possible psychiatric issues in young people with non-cardiac chest pain.